The Immunomodulatory Effect of Cinnamon (Cinnamomum Burmanii) Bark Extract On the C-Reactive Protein (CRP) Level, Leukocyte Count and Leukocyte Type Count of Wistar Rats Exposed to Staphylococcus Aureus - Utomo, Astika Widy; Retnoningrum, Dwi; Gumay, Ainun Rahmasari (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2020)
Introduction: Bacterial infection induces inflammation in human body. This process produceshumoral and cellular immune responses. Cinnamomum burmaniigrows very vast in Indonesia and contains cinnamaldehyde known to have an anti-inflammatory effect.Objective: To prove the effect of C. burmanii bark extract on CRP level, leukocyte count and differential blood count.Methods: Aposttest-only controlled group design with 25 Wistar Rats divided into 5 groups was employed. The CN-G group was giventhe standard feed, the CP-G group was given the standard feed and levamisole 2.5 mg/KgBW, while the CBE-100, CBE-200, and CBE-400 groups were respectively given the standard feed and cinnamon bark extract 100 mg/kgBW, 200 mg/KgBW and 400 mg/KgBW. The treatmentswereconducted for 7 consecutive days.On day 8, all rats were injected with the suspense of S. aureus intraperitoneally. The blood wasthen drawn on day 9, followed with CRP level measurement using the ELISA method. The total leukocyte count and differential blood count weremanually measured.Results: There is no significant difference in the value of CRP level (One Way ANOVA; p = 0.749) with the total counts of leukocytes(p=0.685), monocytes (p=0.769), and eosinophil(p=0.123) between groups. The neutrophils and lymphocytes of CBE-100 group aresignificantly differentfrom the other groups.Conclusion: C. burmanii extract has a potential benefit as immunomodulator.